Arab Donors' Early Response to the Arab Spring - Rouis, Mustapha (World Bank, Washington, DC, 2013)
The World Bank's 2010 study, Arab Development Assistance: four decades of cooperation, and the subsequent note, Arab donors respond favorably to the global financial crisis (Rouis 2011), showed that the three Gulf countries - Kuwait, Saudi Arabia, and the United Arab Emirates (UAE) have provided generous aid financing over the years. This paper, which extends the analysis to 2010 for Arab overseas development assistance (ODA) and to 2011 for the assistance provided by the Arab regional financial institutions, confirms that this generosity continues in the wake of the global economic crisis and the events of the Arab Spring movement. The paper shows that Arab assistance has been responsive in addressing critical development and humanitarian needs in developing countries. There are preliminary indications that Arab donors and financial institutions have made some adjustments in response to the needs of the Arab countries going through the unprecedented political transition sparked by the Arab Spring. Arab donor countries and financial institutions have responded favorably and promptly during the global economic and financial crisis. Their increased assistance to countries affected by the Arab Spring has yet to materialize beyond the stage of pledges and commitments.